Functional and genomic insights into BHET-degrading Stenotrophomonas sp. isolated from the marine plastisphere - Zhuo, Ye; Jin, Chun-Zhi; Lee, Chang-Soo; Lee, Hyung-Gwan (Frontiers in Microbiology, 2025)
Enzymatic degradation of polyethylene terephthalate (PET) has dramatically advanced through protein engineering of PETase, accelerating the biocatalytic depolymerization process. However, the subsequent microbial valorization of PET-derived intermediates, such as bis (2-hydroxyethyl) terephthalate (BHET) and terephthalic acid (TPA), remains limited because of restricted availability and suboptimal activity of specific biocatalytic enzymes. In this study, eight microbial species were isolated from the enriched cultures of marine plastic waste, using 1% PET, BHET and TPA as the sole carbon source. Stenotrophomonas was the only species detected in all the cultures. Strain WED208 was isolated from a BHET-enriched culture and selected for its potential role in plastic degradation. Phylogenetic analysis based on the 16S rRNA gene revealed 99.4% similarity to Stenotrophomonas riyadhensis LMG 33162T; however, it exhibited distinct physiological and genomic features. Strain WED208 degraded approximately 30% of BHET into mono (2-hydroxyethyl) terephthalate (MHET) over 30 days but did not catalyze further conversion to TPA. Comparative analysis identified a putative BHETase (WED208_02958) containing conserved catalytic residues (Ser90, Asp217, and His245). Structural modeling and protein-ligand docking analysis confirmed a key interaction between Ser90 and the ester bond of BHET, supporting the microbial hydrolytic function. Although strain WED208 could degrade neither PET nor TPA, its genome harbored two putative PETase genes and key enzymes potentially involved in TPA degradation, including diol dehydrogenase (tphB), MFS transporter (pcaK), and LysR-type transcriptional regulator (lysR). These findings suggest that WED208 is a promising microbial resource for enzyme engineering and has potential use in microbial consortia to enhance PET biodegradation and upcycling.